Prevalence of Newer β-Lactamases in Gram-Negative Clinical Isolates Collected in the United States from 2001 to 2002 - Ellen Smith Moland; Nancy D. Hanson; Jennifer Ann Black; Ashfaque Hossain; Wonkeun Song; Kenneth S. Thomson (2006)
ABSTRACT Newer β-lactamases such as extended-spectrum β-lactamases (ESBLs), transferable AmpC β-lactamases, and carbapenemases are associated with laboratory testing problems of false susceptibility that can lead to inappropriate therapy for infected patients. Because there appears to be a lack of awareness of these enzymes, a study was conducted during 2001 to 2002 in which 6,421 consecutive, nonduplicate clinical isolates of aerobically growing gram-negative bacilli from patients at 42 intensive care unit (ICU) and 21 non-ICU sites across the United States were tested on-site for antibiotic susceptibility. From these isolates, 746 screen-positive isolates (11.6%) were referred to a research facility and investigated to determine the prevalence of ESBLs in all gram-negative isolates, transferable AmpC β-lactamases in Klebsiella pneumoniae , and carbapenemases in Enterobacteriaceae . The investigations involved phenotypic tests, isoelectric focusing, β-lactamase inhibitor studies, spectrophotometric assays, induction assays, and molecular analyses. ESBLs were detected only in Enterobacteriaceae (4.9% of all Enterobacteriaceae ) and were found in species other than those currently recommended for ESBL testing by the CLSI (formerly NCCLS). These isolates occurred at 74% of the ICU sites and 43% of the non-ICU sites. Transferable AmpC β-lactamases were detected in 3.3% of K. pneumoniae isolates and at 16 of the 63 sites (25%) with no difference between ICU and non-ICU sites. Three sites submitted isolates that produced class A carbapenemases. No class B or D carbapenemases were detected. In conclusion, organisms producing ESBLs and transferable AmpC β-lactamases were widespread. Clinical laboratories must be able to detect important β-lactamases to ensure optimal patient care and infection control.